Bridging the Sustainability Gap: Aligning Consumer Expectations and Corporate ESG Strategies in Indonesia - Lestari, Putri Ayu (Indonesian Scientific Publication, 2024)
Sustainability has become an increasingly salient issue in Indonesia’s consumer and corporate sectors. This study examines the alignment between consumer expectations and corporate readiness in advancing sustainability. It aims to assess how far market demand is matched by corporate ESG initiatives. Using a descriptive analytical method and secondary data sources, this research synthesizes findings from consumer behavior surveys and corporate ESG reporting metrics. Demand side indicators include willingness to pay (WTP), behavioral adoption of sustainable practices, and perceived barriers. Supply side data were drawn from sustainability report filings, ESG index membership, and regulatory frameworks including POJK 51/2017 and SEOJK 16/2021. The findings reveal a high level of consumer engagement with sustainability. About 79% of respondents expressed willingness to pay (WTP) for sustainable goods, while 68% reported behavioral adoption. However, barriers such as availability (44%), lack of information (40%), and affordability (31%) limit broader adoption. On the corporate side, 97% of issuers submitted sustainability reports, but only 111 firms were included in ESG indices, indicating a gap between compliance and strategic ESG integration. This misalignment hinders the development of a fully responsive sustainability ecosystem. The discussion emphasizes that aligning corporate ESG strategies with consumer values yields reputational, competitive, and financial benefits. It also highlights the role of targeted policies and cross sector collaboration in supporting deeper ESG adoption. Educational initiatives and capacity building for SMEs are identified as critical enablers for closing the demand supply gap. In conclusion, the study argues for a paradigm shift from compliance to strategic alignment. Bridging the consumer corporate gap in sustainability will enhance Indonesia’s market resilience and contribute to long term national development goals.